Dramaturgi Pengguna Narkoba di Surabaya - M. Darul Muttaqin; Ali Nurdin (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2019)
This study aims to describe the dramaturgy of drug users in Surabaya. The subjects of this study were three drug users at the PLATO Foundation Surabaya and a drug user outside the foundation that was determined purposively. This type of research is descriptive-qualitative to describe the attitudes and behavior of drug users. Data were collected by interview, observation, and documentation to understand what drug users were doing. Data were analyzed by reducing, classifying, presenting all the information that has been obtained, and drawing conclusions. The results of the study describe that drug users perform roles in different places in the dramaturgy concept, namely the front stage and the front stage. Drug users play a role on the front stage by constructing their own identity with a positive image in front of other people or society. On the other hand, drug users play a back stage role in the form of identity as drug users. This back stage has space for freedom in a limited space for the family and community.